(6 • 2 - 2x + 16) + (4 • 2 + 7x - 55)
(-2x + 16 + 6 • 2) + (7x - 55 + 4 • 2)
(-2x + 16 + 12) + (7x - 55 + 8)
-2x + 28 + 7x - 47
-2x + 7x + 28 - 47
5x + (-19)
5x - 19
So the answer is 5x - 19.
Easy
y=a(x-h)^2+k
vertex is (h,k)
we know that vertex is (4,0)
input that point for (h,k)
y=a(x-4)^2+0
y=a(x-4)^2
passes thorugh the point (6,1)
input that point to find a
1=a(6-4)^2
1=a(2)^2
1=a(4)
divide both sides by 4
1/4=a
thefor the equation is
y=(1/4)(x-4)^2
or
y=(1/4)x^2-2x+4
5x(2y-3)-(y+8)=13 I believe this is correct
Answer:
109,420,982
Step-by-step explanation:
Answer:
h(3b)=12b+4
another answer
h(3b)=4(3b+1)
Step-by-step explanation:
h(x)=4x+4
h(3b)=4(3b)+4
h(3b)=12b+4
if need to simplify..then:
h(3b)=4(3b+1)